Puncture navigation system, positioning support and positioning puncture needle - LI XIANGMIN; WEN YAOFENG; YANG YANG; ZHANG XU (2023)
The invention discloses a puncture navigation system, which comprises a positioning support, at least three space markers, at least one positioning device and at least one positioning device, wherein the positioning support is internally provided with the at least three space markers; the positioning puncture needle is provided with an IMU (Inertial Measurement Unit) positioner; and the imaging unit is used for imaging the punctured part of the subject. The puncture navigation process of the system comprises the following steps: enabling a subject to lie on an examination table, and placing the positioning support on a to-be-punctured part of the subject; irradiating the part to be punctured by a detector of an imaging unit; enabling the positioning puncture needle to face a to-be-punctured part; the navigation unit is used for receiving the attitude angle of the IMU positioner on the positioning puncture needle and combining with an image acquired from the imaging unit to realize path planning and navigation